Studi Pelaksanaan Corporate Social Responsibility (CSR) PT. Sentosa Kalimantan Jaya di Desa Tanjung Batu, Kecamatan Pulau Derawan, Kabupaten Berau, Provinsi Kalimantan Timur: Study of the Implementation of Corporate Social Responsibility (CSR) PT. Sentosa Kalimantan Jaya in Tanjung Batu, Village Derawan Island District, Berau Regency, East Kalimantan Province - Rohani; Sri Ngapiyatun; Erna Rositah; Humairo Aziza; Wartomo; Rusli Anwar (Jurnal Loupe, 2026)
Corporate Social Responsibility (CSR) is an action taken by business people or stakeholders through socially responsible behavior to the community. In carrying out their social responsibilities, business people or companies focus their attention on three things, namely economic, social and environmental. Corporate Social Responsibility (CSR) is an approach where companies integrate social care in their business operations and in interactions with stakeholders based on the principles of volunteerism and partnership. This research aims to analyze the implementation and problems of PT. Sentosa Kalimantan Jaya (PT. SKJ) in the 2018-2022 period in Tanjung Batu Village. This research was conducted from 01 to 12 December 2023 at PT. SKJ. Data collection uses primary data with interview techniques and secondary data in the form of company documents, village documents and other references. PT. SKJ since 2018-2022 has carried out CSR programs for and to the community in the form of assistance in the fields of socio-cultural, religious, facilities & infrastructure, education, infrastructure, and health which are carried out in Tanjung Batu Village, Derawan Island District, Berau Regency, East Kalimantan Province. PT. SKJ has not planned medium-term or short-term CSR programs that were prepared with the community and other stakeholders as a guideline in implementation in the field. In the implementation of PT. SKJ has a problem, namely the submission of follow-up proposals that have actually been submitted to the company and the funds provided are not fully in accordance with the proposals submitted.